Mycotoxins: A Threat to Food Security and Health. - Puri, Sushant; Shingh, Shubham; Tiwari, Preeya (International Journal of Applied Sciences and Biotechnology, 2019)
Multicellular filamentous fungi grown on the surface and inside of moist food secretes toxins in the form of their secondary metabolites which are commonly called mycotoxins. The presence of mycotoxins in food has been a burning issue and a threat to food security and safety. The global population has sky-rocked continues to be, which has created a challenge of providing quality food to the consumers. Aflatoxins, prevalent in most of the food crops in Nepal as well have posed a risk to national food security. Moreover, the consumption of food products containing mycotoxins is a cause of several health hazards like cancer, gastrointestinal problems, and neuropsychiatric effects. Mycotoxins not only has affected humans but also animals. Prevention, decontamination, and inhibition of absorption of toxins have been done in order to manage and mitigate the effects of mycotoxins. Recent research on mycotoxins is focused on the development of new methods to detect and analyze masked mycotoxins obtained from various sources. This review shows the contribution of mycotoxin in the global food security issue as well as its deleterious effects in human and animal health. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 298-303